Seasonal Patterns in Asthma Hospitalization in Saaskatchewan, 1979 to 1989. Issue 5 (3rd October 1997) - Meleth, Sreelatha; Senthilselvan, A
Abstract : OBJECTIVES: To determine whether monthly asthma hospitalization rates in Saskatchewan exhibited a seasonal pattern. Rates were studied from January 1979 to December 1989. PATIENTS: The age groups studied were aged birth to four years, aged five to 14 years, 15 to 34 years, 35 to 49 years and 50 to 65 years. Sex differences in seasonal patterns in asthma hospitalization rates were also investigated. METHODS: The hospitalization data for asthma were obtained for the province of Saskatchewan from 1979 to 1989, inclusive. The time series was decomposed into its trend, seasonal and error component, using an additive model. Significance of the components was tested using a two-way ANOVA. RESULTS: Seasonal variations were observed in the monthly asthma hospitalization rates among Saskatchewan residents. Increases in asthma hospitalization rates were observed in the spring and fall months among children, in summer months among young adults aged 15 to 34 years and in winter months among the older age groups. Seasonal patterns in asthma hospitalization rates were similar for males and females in children and in adults aged 50 to 64 years. In young adults aged 15 to 34 years, increased asthma hospitalization rates were observed in spring months among men and in both spring and fall months among women. The 35- to 49-year-old men did not exhibit a statistically significant seasonal pattern, whereas the women did. No sex differences in seasonal patterns of asthma hospitalization rates were statistically significant. CONCLUSIONS: Seasonal patterns were observed in asthma hospitalization rates for residents of Saskatchewan. Asthma hospitalizations were greater in spring and fall seasons for children and in winter for the older adults. More studies are required to examine possible reasons for these seasonal differences in asthma hospitalizations.